Effectiveness of Group Cognitive Behavior Therapy (CBT) with Mindfullness on Depression and Clinical Outcomes in Hemodialysis Patients - Hasanah, Uswatun; Noh, Malehah Mohd; Arsat, Norkiah (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Hemodialysis patients experience many stressors related to the medical procedures they undergo. This causes various psychological problems in patients, including depression. Patients' psychological problems can affect their physical conditions, one of them is clinical outcomes. Objective: The purpose of this study was to determine the effect of Group CBT with mindfulness on depression and clinical outcomes of hemodialysis patients in Jendral Ahmad Yani Hospital. Method: A quasi-experiment with a pre-post test design and a control group was the study methodology employed. Data from patients who reported depression in the intervention group were assessed both before and after the group CBT with mindfulness intervention. Consecutive sampling was used to create the research sample, which included 66 respondents in total 33 for the intervention group and 33 for the control group. BDI II was the research tool utilized to measure depression’s score. Before and after CBT, depression scores and clinical outcomes were measured. For statistical testing, the paired t test was utilized for depression and the Wilcoxon test for clinical outcomes. Results: According to the findings, depression significantly declined in the intervention group compared to the control group (p-value: 0.000), and improved clinical outcomes results (p-value: 0.000) after CBT. Conclusions: Group CBT with mindfulness effectively reduces the level of depression and improve clinical outcomes of patients to be better. By providing specialized nursing interventions, the hemodialysis room can work to improve clinical outcomes for hemodialysis patients, reduce depression, provide comprehensive and high-quality nursing care that is integrated into their health services.